میرمہدی حسین مجروؔ ح :تحقیق و تنقید: Meer Mehdī Ḥussain Majroḥ: Research & Critical Study (Al-Qamar, 2021)
Majrooh is considered amongst the famous disciples of Ghālib. Ghālib,s many renowned letters are attributed or addressed to him Occasionally he gained knowledge of classical poetry and practiced it in his Diwān “Mazhar-e-Muāni”- His Diwān depicts typical classic touch of Poetry. His language is simple and soft, with the usage of small rhythms, he masterly revives old tradition of Urdu poetry. Most of his ghazals,ie have simplicity close near to  Meer Taqī Meer. We can tell him the last sorrower of Dehli by his poetry.
Keywords: Mazhar-e-Muani; Meer Faqeer–ul-Allah Faqeer; Nawab Rāmpur; Mirza Ghalib; Gul-e-Sadbarg